Development of a methodology to rearing and multiplication of Aphis gossypii: advances and successes - Oliveira, José Eudes de Morais; De Bortoli, Sergio Antonio; Santos, Rafael Ferreira dos; Moreira, Andréa Nunes (Comunicata Scientiae, 2010)
Studies on several ways to control pests and use of natural enemies require arthropods in quantity and quality. Through this need, the process of rearing and multiplication of arthropods has over the years, going through significant changes. Techniques for rearing and multiplication of insects are very important for biological studies of insect pests and methods of control. To establishment and definition of a methodology for multiplication has been a great challenge in studies of biology and rearing of insects, mainly due to the difficulty of its establishment of the populations in green house and field conditions. To adjust a methodology for multiplication of Aphis gossypii (Hemiptera: Aphididae) it was established a colony this is insects in laboratory conditions under cotton plants (Gossypium hirsutum L. cv. latifolium Hutch). This methodology has as objective high survival and the improvement of the use of plants for a longer period. With the development of techniques and resources used in the rearing, it was observed an increase in the number of individuals from the better use of plants and lower costs. The rearing was maintained in plants under conditions of laboratory and protected to prevent the migration and infestation of other species of aphids and natural enemies. After the establishment of the rearing it was observed the total control of the parasitism of A. gossypii under experimental conditions.